2022
DOI: 10.1039/d2py00271j
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the molecular weight and size distribution of PSS on mixed ionic-electronic transport in PEDOT:PSS

Abstract: The commercially available polyelectrolyte complex poly(3,4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) is ubiquitous in organic and hybrid electronics. As such, it has often been used as a benchmark material for fundamental studies and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 73 publications
1
39
0
2
Order By: Relevance
“…As a result, the overall increase in the conductivity upon complexation is dominated by the pre-factor, σ 0 , that is indicative of the long-range connectivity among conductive sites. Our observations support conclusions from prior studies that long-range connectivity is more important than local ordering. ,, …”
Section: Resultsmentioning
confidence: 99%
“…As a result, the overall increase in the conductivity upon complexation is dominated by the pre-factor, σ 0 , that is indicative of the long-range connectivity among conductive sites. Our observations support conclusions from prior studies that long-range connectivity is more important than local ordering. ,, …”
Section: Resultsmentioning
confidence: 99%
“…Using PEDOT:PSS as a mixed ionic− electronic conductor, it was reported that the molecular weight distribution (MSD) (as opposed to the average molecular weight) of the ionic species [polystyrene sulfonate (PSS)] is a critical parameter influencing the ionic−electronic conductivity of the matrix. 14 In this context, it may be important to emphasize the crystallization behavior of PEO. This polymer (PEO) can form highly crystalline domains at high molecular weights, thus restricting the movement of ions (limiting the penetration of ions in the crystalline domains) 8 compared to the relative ease of ion-movement in the amorphous PSS-rich domains.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They concluded that the ionic–electronic conductivity can be tuned by manipulating the combination of electronic and ionic components within a hybrid composite. Using PEDOT:PSS as a mixed ionic–electronic conductor, it was reported that the molecular weight distribution (MSD) (as opposed to the average molecular weight) of the ionic species [polystyrene sulfonate (PSS)] is a critical parameter influencing the ionic–electronic conductivity of the matrix . In this context, it may be important to emphasize the crystallization behavior of PEO.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated theoretically and experimentally that the template molecular weight (M w ) plays an important role in determining the build-up kinetics of PEDOT complexes and thus the physico-chemical properties. [25][26][27][28] However, precious little attention has been paid to the template M w effect on g s (see Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%